Analisis Dampak Kebijakan Ekonomi Terhadap Pertumbuhan Usaha Mikro Kecil dan Menengah (UMKM) di Era Digital - YASMANLIZAR (Sebi : Studi Ekonomi dan Bisnis Islam, 2024)
This study aims to evaluate the impact of economic policies implemented to support the digitalization and modernization of SMEs in Indonesia. The primary focus of this study is to understand how these policies affect the growth of SMEs, specifically chili farmers like Mr. Jayadi, as well as other SME sectors. This research employs a mixed-methods approach, combining both quantitative and qualitative methods to provide a comprehensive overview. The quantitative method involves surveys of various SMEs to measure changes in technology adoption, revenue, and market expansion following the implementation of the policies. Descriptive statistics and regression analysis are used to assess the relationship between the policies and SME performance. Meanwhile, qualitative methods through in-depth interviews and focus group discussions (FGD) are used to explore subjective insights and challenges faced by SMEs in policy implementation. The main findings indicate that policies supporting the digitalization of SMEs have successfully enhanced technology adoption, expanded market reach, and increased revenue. However, challenges such as limited infrastructure in remote areas, knowledge gaps, and complicated administrative processes persist. This study also identifies areas that need further research, including the impact of policies on specific sectors and regions. The study recommends a mixed-methods approach in future research methodology and long-term evaluation to gain a deeper understanding of the policy impacts. The results of this study are expected to provide a basis for policy improvement and more effective support for SMEs in Indonesia.